Pendampingan Orang Tua dalam Mengembangkan Sosial Emosional Anak di Masa Pandemi Covid-19 di Desa Aek Jangkang Kabupaten Padang Lawas Utara Tahun Ajaran 2020/2021 - Muhibbatul Hikmah Harahap; Khadijah Khadijah; Zulkipli Nasution (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Children's social and emotional development from an early age is an important foundation for the formation of their character, attitudes and behavior in the future. This research aims to find out how parents in AekANGKAng Village, North Padang Lawas Regency, support and foster the social emotional development of their children during the Covid-19 pandemic. Using a phenomenological approach, this research examines in depth the experiences of parents and children in this context. The results show that parental guidance is very important in helping children's social emotional development and shaping their future direction. Actions that parents can take include: Taking an active role in their children's education during the pandemic, Scheduling time for activities with the family, Creating a safe and comfortable environment for family interaction. This research emphasizes the important role of parents in supporting children's social and emotional development, especially in challenging situations such as the Covid-19 pandemic. By providing special attention and creating a conducive environment, parents can help their children develop social and emotional skills that are important for their future.